2022
DOI: 10.1158/0008-5472.can-21-3552
|View full text |Cite
|
Sign up to set email alerts
|

The Prostate Cancer Androgen Receptor Cistrome in African American Men Associates with Upregulation of Lipid Metabolism and Immune Response

Abstract: African American (AA) men are more likely to be diagnosed with and die from prostate cancer (PCa) than European American (EA) men. Despite the central role of the androgen receptor (AR) transcription factor in PCa, little is known about the contribution of epigenetics to observed racial disparities. We performed AR ChIP-seq on primary prostate tumors from AA and EA men, finding that sites with greater AR binding intensity in AA relative to EA PCa are enriched for lipid metabolism and immune response genes. Int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 64 publications
1
16
2
Order By: Relevance
“…Recently ( 40 ), shared androgen receptor (AR) binding has been established between primary EA prostate cancer samples and prostate cancer cell lines, such as LNCaP, supporting cell line research utility. To complement this, we reasoned that cell lines may reflect primary prostate tissue in an ancestry-dependent manner and therefore we measured the similarity between RC43N cells and nonmalignant AA prostate epithelium, by examining the genomic overlap between chromatin accessibility in cell lines and AR cistrome in primary tissues ( 41 ). These analyses demonstrated that the RC43N and RC43T very significantly overlapped with AA nonmalignant prostate and prostate cancer AR cistromes, but not the EA prostate cancer AR cistrome, and LNCaP most significantly overlapped with the EA prostate cancer AR cistrome ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently ( 40 ), shared androgen receptor (AR) binding has been established between primary EA prostate cancer samples and prostate cancer cell lines, such as LNCaP, supporting cell line research utility. To complement this, we reasoned that cell lines may reflect primary prostate tissue in an ancestry-dependent manner and therefore we measured the similarity between RC43N cells and nonmalignant AA prostate epithelium, by examining the genomic overlap between chromatin accessibility in cell lines and AR cistrome in primary tissues ( 41 ). These analyses demonstrated that the RC43N and RC43T very significantly overlapped with AA nonmalignant prostate and prostate cancer AR cistromes, but not the EA prostate cancer AR cistrome, and LNCaP most significantly overlapped with the EA prostate cancer AR cistrome ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Even as modern clinical research has brought improvements in medical care across multiple diseases, for minority groups, outcomes continue to lag in numerous health domains. 1 In certain diseases, outcome disparities may be a composite result of genetic and environmental factors, 2,3 and research efforts lacking in diversity leave the medical community catching up to understand that interplay. In the United States specifically, some examples highlight how societal drivers appear to play a major role in health disparities.…”
Section: Diversity Equity and Inclusion In Clinical Research: A Path ...mentioning
confidence: 99%
“…In certain diseases, outcome disparities may be a composite result of genetic and environmental factors, 2,3 and research efforts lacking in diversity leave the medical community catching up to understand that interplay. In the United States specifically, some examples highlight how societal drivers appear to play a major role in health disparities.…”
mentioning
confidence: 99%
“…Where nutrient availability is consistently changing during tumor progression, cancer cells in the TME harness lipid metabolism to support their rapid proliferation, survival, migration, invasion, and metastasis. [46][47][48] Berchuck et al 49 elegantly demonstrated that tumors from AA patients had a distinct differential AR cistrome and greater AR binding intensity at sites enriched for lipid metabolism and immune response genes. Another exciting discovery by Elkenawi et al 50 is on the role of ANPEP in prostate cancer of AA patients.…”
Section: Mitochondrial Regulation Of Macrophagetumor Cell Metabolic I...mentioning
confidence: 99%